Factors Determining the Provision of Psychosocial Services for Oncological Patients and Their Loved Ones in Lithuania - Gaidytė, Emilija; Dunajevas, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2019)
It is acknowledged by various organizations, experts, and researchers around the world that meeting psychological and social needs is an important factor in cancer treatment. However, there is a shortage of psychosocial care supply for cancer patients and their family members in Lithuania. The aim of this study is to discern the causes of this insufficient supply. In order to find out the possible causes, Jon Elster’s action explanation framework was used. According to the framework, it is possible to deduce these factors: institutional constraints, economical (resources and labor supply) constraints, social preferences, and political preferences. Qualitative research (expert interviews) and secondary data analysis research methods were employed to gather the required data. A data analysis shows that the there are no institutional constraints for the provision of psychosocial care. However, there is a lack of public resources dedicated for the provision of psychosocial care. As a consequence, the main providers of psychosocial care for cancer patients and their family members are NGOs, which heavily depend on volunteer labor force. There is a contradiction in the point of view toward the professionalization of psychosocial care provision. It is the natural position of medical professionals that the provision of psychosocial care should be in the hands of professionals. On the other side, NGOs disagree with such a perspective. The need for psychosocial care is verbalized by experts and professionals; however, the general public prefers medical treatment. Thus, it is understandable why the public resources allocated to the provision of psychosocial care are so scarce. It is also evident that the political parties are not interested in psychosocial care, as it was shown by our analysis of their political programs.